Chemoenzymatic Synthesis of D‐Glucaro‐δ‐lactam Containing Oligosaccharides as Putative Heparanase Inhibitors. Issue 42 (9th November 2021) - Ni, Minghong; Stancanelli, Eduardo; Kayal, Yasmin; Candido, Marialuisa; Guerrini, Marco; Vlodavsky, Israel; Naggi, Annamaria; Liu, Jian; Petitou, Maurice
Abstract: Heparanase is an endo‐β‐glycosidase that cleaves heparan sulfate chains at the level of the glycosidic bond of selected glucuronic acid residues. Heparin fragments, that can compete with heparan sulfate for binding to heparanase, have been reported as weak heparanase inhibitors. To reinforce their inhibitory activity, a known β‐glucuronidase inhibitor has been introduced at their reducing end to directly interfere with the active site of the enzyme. We report here the synthesis of such oligosaccharides, displaying D‐glucaro‐δ‐lactam at their reducing end. Thanks to the trichloroacetimidate glycosylation method, we could devise experimental conditions allowing O‐glycosylation of the lactam ring, and we thus chemically prepared trisaccharides that were further elongated and sulfated using enzymatic methods. Heparanase inhibitory activity was not significantly improved by the presence of the D‐glucaro‐δ‐lactam ring. Abstract : Putative heparanase inhibitors were designed, consisting of an oligosaccharide displaying a β‐glucuronidase inhibitor at their reducing end. Their synthesis involved glycosylation of D‐glucaro‐δ‐lactam derivatives. Using trichloroacetimidate glycosylation, the desired O‐glycosylation of the lactam ring took place in competition with formation of complex imidates. Trisaccharides were obtained and further elongated using enzymatic methods.